Improved Wear-Resistant Coatings

By increasing the content of hard-phase carbide materials and improving the spraying process in WC-based spray coating, low-oxide and low-pore coatings are prepared, which solves the problem of insufficient wear resistance of existing WC-based coatings under severe micro-wear conditions, and achieves higher wear resistance and longer service life.

JP7657843B2Active Publication Date: 2025-04-07PRAXAIR ST TECHNOLOGY INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023015090
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-14
Filing Date
2023-02-03
Publication Date
2025-04-07
Estimated Expiration
2043-02-03

AI Technical Summary

Technical Problem

Existing WC-based spray coatings cannot meet the wear resistance requirements of emerging applications when faced with more severe micro-wear conditions.

Method used

A modified coating structure is adopted, the hard-phase carbide material content in the coating is 83-94% by volume, the remaining metal bonding agent, and a low oxide and low pore coating is prepared by an improved high-speed spraying process, combined with one or more inert gases.

Benefits of technology

Significantly improves the wear resistance and wear resistance of the coating, reduces wear of metal bonding agents, extends the life of the coating, and reduces the need for replacement or repair coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657843000002
    Figure 0007657843000002
  • Figure 0007657843000003
    Figure 0007657843000003
  • Figure 0007657843000004
    Figure 0007657843000004
Patent Text Reader

Abstract

To provide an improved abrasion resistant coating for a new application accompanying a severe fine abrasion condition.SOLUTION: Provided is an improved abrasion resistant coating based on a new abrasion resistance coefficient (R) for a predetermined average size of abrasive fine particles. The improved abrasion resistant coating shows an improved abrasion resistance and a hardness and shows a minimum oxide content and a minimum porosity. The improved abrasion resistant coating is produced with a composite material composed of a hard phase and a metal bonding agent in a powder particle size range of about 0.5 μm-30 μm as a part of a modified spray coating process.SELECTED DRAWING: Figure 1B
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority to U.S. Provisional Patent Application No. 63 / 353,217, filed June 17, 2022, the disclosure of which is incorporated by reference in its entirety herein.

[0002] The present invention relates generally to improved wear resistant thermal spray coatings. In particular, the resulting coating structure is substantially free of oxide content and porosity, combined with a reduced mean free path of the metal binder, such that a substantial portion of the fine abrasive particles cannot erode and remove the binder. [Background technology]

[0003] Tungsten carbide (WC) based thermal spray coatings are known to exhibit favorable wear resistance. Such coatings are widely used in industrial applications such as aviation and oil and gas where abrasive conditions are problematic. However, new applications are emerging that present even more severe microabrasive conditions, whereby conventional WC based thermal spray coatings cannot provide satisfactory performance against the finer wear particles. Summary of the Invention [Problem to be solved by the invention]

[0004] Given the inadequacies of conventional WC-based thermal spray coatings for emerging applications involving severe microwear conditions, there exists an unmet need for improved wear resistant coatings.

[0005] The present invention may include any of the following aspects in various combinations, and may also include any other aspects of the invention described below in the written description.

[0006] Other aspects, features and embodiments of the present disclosure will become more fully apparent from the following description and the appended claims.

[0007] In a first aspect, there is provided an improved coated article for use in producing a battery electrode material containing fine abrasive particles, the improved coated article comprising an article adapted for contact with fine abrasive particles, and a wear-resistant coating on a surface of the article, the wear-resistant coating comprising one or more hard phases of a carbide-based material in a proportion of 83-94 weight percent based on a total weight of the coating, with the balance being a metallic binder, the wear-resistant coating ensuring that a majority of the fine abrasive particles adapted for contact with the improved coated article are located on the hard phases, thereby reducing or minimizing contact between the fine abrasive particles and the metallic binder, the wear-resistant coating having a wear resistance coefficient designated as (R), the wear resistance coefficient (R) being defined as the ratio of the average size of the fine abrasive particles to the mean free path of the metallic binder.

[0008] In a second aspect, an enhanced wear resistant coating having a porosity of less than about 1 volume percent and an oxide content of less than about 2.5 volume percent, the coating being thermally sprayed by a modified high velocity thermal spray process using a mixture of fuel and oxygen and one or more inert gases using fine powder particles in the range of about 0.5 to about 30 microns, the coating further comprising a hard phase and a metallic binder, whereby the coating has a wear resistance factor designated as (R), the wear resistance factor (R) being defined as the ratio of the average size of the fine abrasive particles to the mean free path of the metallic binder, the wear resistance factor (R) having a value in the range of about 1 to about 65 for a corresponding average size of the fine abrasive particles in the range of about 0.5 to 15 microns.

[0009] In a third aspect, there is provided an enhanced wear resistant coating suitable for protection against fine abrasive particles, the wear resistant coating having a porosity of less than about 1 volume percent and an oxide content of less than about 2.5 volume percent, the wear resistant coating comprising a hard phase and a metal bond, the coating configured to substantially reduce wear loss of the metal bond with a wear resistance factor designated as (R), defined as the ratio of the average size of the abrasive fine particles to the mean free path of the metal bond, the wear resistance factor having a value in the range of about 1 to about 65, provided that when the average size of the abrasive fine particles is about 0.5, the wear resistance factor (R) is in the range of about 1 to about 3, provided that an abrasion resistance factor (R) in the range of about 2 to about 4 when the average abrasive microparticle size is about 0.75, except that when the average abrasive microparticle size is about 1 micron, the abrasion resistance factor (R) is in the range of about 3 to about 5, when the average abrasive microparticle size is about 2 to about 3 microns, except that when the average abrasive microparticle size is about 2 to about 3 microns, the abrasion resistance factor (R) is in the range of about 6 to about 14, when the average abrasive microparticle size is about 4 to about 7 microns, except that when the average abrasive microparticle size is about 8 to about 15 microns, the abrasion resistance factor (R) is in the range of about 25 to about 65. [Brief description of the drawings]

[0010] The objects and advantages of the present invention will be better understood from the following detailed description of a preferred embodiment thereof when taken in conjunction with the accompanying drawings in which like numerals refer to like features throughout. [Figure 1A] FIG. 1A is an illustration of a conventional wear resistant coating that is subject to rapid wear and erosion. [Figure 1B] FIG. 1B is an illustration of an improved wear resistant coating in accordance with the principles of the present invention capable of enhanced fine abrasive particle and erosion resistance. [Diagram 2] FIG. 2 is an optical micrograph at 500x magnification of an improved abrasion resistant coating according to the principles of the present invention as described in Example 1. [Diagram 3]FIG. 3 is an optical micrograph at 500x magnification of an improved abrasion resistant coating according to the principles of the present invention as described in Example 2. [Figure 4] FIG. 4 is an optical micrograph at 500x magnification of a conventional abrasion resistant coating as described in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The relevance and function of the various elements of the embodiments will be better understood from the following detailed description, which contemplates various permutations and combinations of features, aspects, and embodiments as being within the scope of the disclosure. Thus, the disclosure may be specified as comprising, consisting of, or consisting essentially of any such combinations and permutations of these specific features, aspects, and embodiments, or a selected one or more of them.

[0012] When a range of values ​​describes a parameter, all subranges, point values, and endpoints within or defining that range are expressly disclosed herein. All physical property, dimension, and ratio ranges and subranges between the range endpoints of those properties, dimensions, and ratios (including the point values ​​and endpoints) are considered to be expressly disclosed herein.

[0013] Unless otherwise expressed herein and throughout, all percentages are volume percentages based on the total volume of the coating.

[0014] As used herein and throughout, "battery electrode material" refers to any material, including precursors and raw materials, that are involved in the processing and manufacture of the final battery electrode material, including but not limited to LiCoO2, Li(NiCoMn)O2, Li(NiCoAl)O2, LiMn2O, and LiFePO4.

[0015] "Metallic binder" as used herein and throughout means a phase in an abrasion resistant coating that is soft compared to a hard phase in the same coating.

[0016] "Fine abrasive particles," as used herein and throughout, is intended to refer to relatively small diameter abrasive particles having a median size range of about 0.5 um to about 15 um as measured by laser diffraction, which are typically used in applications such as, but not limited to, the preparation and manufacture of battery electrode materials.

[0017] "Article" as used herein and throughout includes, but is not limited to, mixing equipment components such as blades and containers, slot dies, gravure rollers, calendar rollers, and any other surface of a part or component requiring a protective coating such as the improved wear resistant coating of the present invention.

[0018] "Average size" as used herein and throughout means particles having a median size as can be measured by the standard technique known as laser diffraction.

[0019] As used herein and throughout, "Ra" means the arithmetic mean of the absolute values ​​of the roughness profile ordinates.

[0020] As used herein and throughout, "Rmax" means the maximum single roughness depth within the evaluation length.

[0021] The drawings are for purposes of illustrating the invention and are not intended to be drawn to scale. The embodiments will be described with reference to the drawings in which similar elements are referenced by like numerals. Certain features may be purposely omitted in each of the drawings to better illustrate various aspects of the novel wear-resistant coating. The embodiments are described by way of example only, and the invention is not limited to the embodiments shown in the drawings.

[0022] In many applications where conventional wear-resistant coatings are used to produce various materials and articles, such as battery electrode materials, they may be in contact with fine abrasive particles. However, when contacted with fine abrasive particles, conventional wear-resistant coatings may wear rapidly. The present inventors have recognized that the high wear of conventional wear-resistant coatings is generally due to preferential wear of the metal binder within the coating. The metal binder may be susceptible to wear loss due to abrasion and erosion as a result of contact with the fine abrasive particles. In particular, the mean free path of the metal binder is sufficiently large that a greater amount of fine abrasive particles may undesirably come into contact with the metal binder. To further illustrate this phenomenon, FIG. 1A shows an illustration of a conventional wear-resistant carbide coating 20 including hard carbide particles 11 dispersed within the metal binder 10. The hard carbide particles 11 are spaced apart sufficiently to allow the mean free path of the metal binder 10 to accommodate a significant portion of the relatively small fine abrasive particles 12a. Due to the large proportion of fine abrasive particles 12a that may typically come into contact with the metal bond 10 of conventional wear resistant coatings 20, the metal bond 10 may be rapidly removed, thereby causing unacceptably high wear and erosion material loss of the coating 20.

[0023] The inventors have therefore recognized the need for an improved wear-resistant coating. The present invention has emerged as a result of the failure of conventional wear-resistant coatings, such as that illustrated in FIG. 1A, to effectively protect against abrasive and erosive wear on various surfaces of articles that come into contact with fine abrasive particles during processing of the fine abrasive particles into various films and materials. The inventors have found that intentionally reducing the distance between the hard phases in the wear-resistant coating allows the contact of the fine abrasive particles with the metal binder to be reduced or minimized. The result is enhanced wear and erosion resistance, since the hard phases are not significantly subjected to abrasion by the fine abrasive particles. FIG. 1B shows an illustration of an improved wear-resistant carbide coating 20' suitable for protection against fine abrasive particles. The distance between the hard carbide particles 11' is reduced compared to that of FIG. 1A to allow a greater proportion of the fine abrasive particles 12a' to be located above the hard carbide particles 11'. The reduced particle spacing of adjacent or proximate hard carbide particles 11' creates a smaller mean free path of the metal bond 10', thereby making it more difficult for the fine abrasive particles 12a' to contact the metal bond 10', as compared to the conventional wear-resistant coating of FIG. 1A. The net effect is a substantial reduction or elimination of the fine abrasive particles in the metal bond 10', which leads to significantly reduced wear of the coating 20' due to rapid metal bond removal. As a result, an extended life of the coated article that encounters the fine abrasive particles 12a' during various processing steps is achieved. The need for recoating or repair of the surface of the article due to rapid wear of the coating 20' is substantially reduced. The reduced spacing between the hard phases can be achieved by loading the coating with more hard phase per unit volume, thereby increasing the total volume fraction of the hard phase. Alternatively, or in addition, the reduced spacing can be achieved by the use of a smaller particle size of the hard phase.

[0024] According to the principles of the present invention, the improved wear-resistant coating of the present invention provides optimized wear and erosion resistance compared to conventional wear-resistant coatings. The improved wear-resistant coating of the present invention is formulated to exhibit a specific wear coefficient designated as (R), defined as the ratio of the average size of the fine abrasive particles (typically expressed in units of microns, μm) to the mean free path of the metal binder (typically expressed in units of microns, μm). The mean free path as shown in Figures 1A and 1B represents the average of the distance between the edges of adjacent hard phase particles (11, 11') embedded in the soft phase binder (10, 10'), as indicated by the various arrows. The mean free path is preferably calculated using Fiji Image software, an open source image analysis software based on ImageJ, independently developed by the National Institute of Health and accessible at https: / / imagej.net / software / fiji / / . The software can be used to measure the linear distance in the x and y directions between the phases after the image is converted to a black and white image. The wear resistance factor (R) is dimensionless and is a significant new design criterion of the present invention in formulating improved wear resistant coatings. The R value is a reliable measure of the expected performance of a coating against wear and erosion resulting from the coating being in contact with a specific fine abrasive particle of a given size. A range of R values ​​is provided for a given average size of fine abrasive particle in contact with the coating for a particular application.

[0025] In one embodiment of the present invention, an article is coated with an improved wear-resistant coating for making battery electrode materials from fine abrasive particles. The wear-resistant coating preferably comprises about 83-94% by weight of a carbide-based material based on the total weight of the coating, with the remainder being a metal binder. The wear-resistant coating comprises hard carbide-based particles and a metal binder. The article is preferably a calender roll that contacts the fine abrasive particles and compresses the fine abrasive particles into a film to make a battery electrode material of a specific chemical composition. The wear resistance factor (R) in such applications has a value ranging from about 1 to about 65 for a corresponding average size of the fine abrasive particles ranging from about 0.5 to 15 microns. Specifically, the coating is designed or tailored to exhibit R min and R max values ​​for a specific average size of the abrasive particles, as shown in Table 1 below.

[0026] [Table 1]

[0027] For fine abrasive particles having a size (i.e., average size) of 0.5 microns, the coating is formulated to have an R value in the range of about 1 to about 3. For fine abrasive particles having a size of about 0.75 microns, the coating is formulated to have an R value in the range of about 2 to about 4. For fine abrasive particles having a size of about 1 micron, the coating is formulated to have an R value in the range of about 3 to about 5. For fine abrasive particles having a size of about 2 to 3 microns, the coating is formulated to have an R value in the range of about 6 to about 14. For fine abrasive particles having a size of about 4 to 7 microns, the coating is formulated to have an R value in the range of about 12.5 to about 30. For fine abrasive particles having a size of about 8 to 15 microns, the coating is formulated to have an R value in the range of about 25 to about 65.

[0028] In this manner, the mean free path of the metal binder is determined based on the average size of the fine abrasive particles that contact the calender roll. A given R value as shown in Table 1 allows the majority of the fine abrasive particles that contact the coated article (e.g., the coated calender roll) to be located on the hard phase of the coating, thereby reducing or minimizing the contact of the fine abrasive particles with the metal binder. As a result, the life of the coated calender roll is extended, thereby reducing the need for replacement of the calender roll. Other benefits include less surface roughness and profile change of the original coated calender roll. As a result, the quality of the battery electrode material is consistent over a longer period of time, thus improving production yield and reducing quality non-conformity.

[0029] Any suitable type of chemical composition may be used for the fine abrasive particles. In one embodiment, the fine abrasive particles include lithium ions to create a battery electrode material.

[0030] It should be understood that Table 1 represents one specific example of an application for making battery electrode materials, and the principles of the present invention are applicable to formulating coatings for protection against any fine abrasive particles utilized to make materials and films in other applications.

[0031] The hard phase of the wear resistant coating may comprise any carbide based material, including but not limited to WC, CrC, (W,Cr)C, TiC, VC, NbC, B4C, SiC, diamond, or combinations thereof, and the metal binder may comprise any metal based material, including but not limited to Co, CoCr, Ni, NiCr, Mo, Fe, FeCrAl, FeCr, FeB, FeAl, TiAl, Ti, or combinations thereof. Any combination of hard phases and metal binders is contemplated. In alternative embodiments, the hard phase may comprise non-carbide based materials, such as various nitrides. The hard phase may be in any suitable amount, including 83-94% by weight, based on the total weight of the coating.

[0032] In addition to excellent abrasion and erosion wear, the coating of the present invention exhibits minimal porosity and minimal oxide content. In one embodiment, the coating exhibits an oxide content of less than about 2.5 vol.%, more preferably less than about 1 vol.%, and most preferably less than about 0.5 vol.%, based on the total volume of the coating. The porosity is less than about 1 vol.%, more preferably less than about 0.5 vol.%, and most preferably less than about 0.3 vol.%, based on the total volume of the coating. The reduction or elimination of oxides and porosity can result in the reduction or elimination of localized defects in the surface finish of the coated article. In addition, the lack of oxides and porosity also helps improve the hardness and ductility of the coating. The coating hardness is preferably less than about 950 HV. 300g More preferably, about 1200HV 300g More than 1350HV, most preferably about 1350HV 300g It is characterized by a Vickers hardness of .

[0033] The improved wear resistance of the coating may be produced from a modified high velocity thermal spray process. The powder feedstock consists of fine particles ranging from about 0.5 to about 30 microns, which is impractical for use in conventional thermal spray processes. Preferably, the improved wear resistant coating is formed using a modified high velocity oxygen fuel ("HVOF") process that uses an inert gas to premix with oxygen, as described in applicant's U.S. Patent Application Publication No. 2020 / 048753, the details of which are incorporated herein by reference in their entirety for all purposes.

[0034] Several experiments were performed to verify the improved wear resistant coating. In accordance with the principles of the present invention, certain test coatings were prepared with reduced particle spacing to create a wear resistance factor designated as R based on the abrasive test media used. The coatings of the present invention were prepared using a modified HVOF process described in applicant's U.S. Patent Application Publication No. 2020 / 048753.

[0035] The binder mean free path of the test coatings was measured using the image analysis software Fuji (ImageJ). This software was able to measure the average linear distance of the metal binder after the image was converted to black and white. The mean free path was calculated from the average linear distance and the R value was determined based on the test use of a fine abrasive medium of alumina square powder with an average size of 5 microns.

[0036] Abrasion performance evaluation was performed by the applicant by utilizing a rotary wet wheel abrasion test. The test was primarily based on the ASTM G105 standard with the following modifications: (i) utilization of a modified rubber wheel having a diameter of about 216 mm and a width of 12.7 mm, (ii) 3000 revolutions of the wheel at 50 RPM, (iii) an abrasive medium of 5 micron alumina square powder, (iv) a test slurry prepared by mixing 1200 g of alumina powder (+ / - 2 g) and 700 g of deionized water (+ / - 2 g), and (v) a coated sample that was abraded to a surface finish of about 20 to about 40 μm (Ra) prior to testing. The test specimen was exposed to the fine abrasive medium in the test slurry. The face of the coated sample was pressed against the modified rubber wheel and abraded by the fine abrasive particles in the test slurry to simulate abrasion of the coating. A 5 micron alumina square powder was used to simulate more severe fine abrasion conditions. The test was performed at 3000 revolutions using the modified rubber wheel. The samples were weighed before and after testing on a digital weighing scale with an accuracy level of 0.0001 g, and the results were converted to volume loss through use of the specific gravity of the coating material.

[0037] The initial and final roughness of the samples were measured using a Mahr S2 Perthometer. The roughness profiles were evaluated and characterized by Ra and Rmax values.

[0038] Example 1 A carbide-based coating of the present invention having a proportion of 94% by weight WC and 6% by weight Co was prepared and tested as described above. The coating was determined to have a mean free path of 0.30 microns. The coated specimens prior to wear testing were observed to exhibit minimal porosity and minimal oxide content based on optical microscopy analysis. Figure 2 shows an optical micrograph of the coating at a magnification of 500x. No coating oxides or coating porosity were observed in Figure 2. The hardness was measured at 1500HV. 300g The coating of FIG. 2 was subjected to abrasion testing (as described above) and the abrasion resistance factor (R) of the coating was determined to be 16.7, based on contact of the coating with a fine abrasive medium of 5 micron alumina square powder. A rotary wet wheel abrasion test yielded a wear resistance of 0.122 mm per 1000 revolutions. 3 A wear scar was revealed with a volume loss of material of 0.019 μm Ra and 0.433 μm Rmax after microabrasion testing. Testing confirmed that coatings prepared according to the R values ​​as shown in Table 1 exhibited a reduced amount of coating loss compared to conventional wear resistant coatings. The surface roughness of the wear scar was measured to increase by only 0.019 μm Ra and only 0.433 μm Rmax after microabrasion testing.

[0039] Example 2 A carbide-based coating of the present invention having a proportion of 86 wt. % WC, 10 wt. % Co, and 4 wt. % Cr was prepared and tested as described above. The coating was determined to have a mean free path of 0.253 microns. The coated specimens prior to wear testing were observed to exhibit minimal porosity and minimal oxide content based on optical microscopy analysis. Figure 3 shows an optical micrograph of the coating at 500x magnification. No coating oxides or coating porosity were observed in Figure 3. The hardness was measured at 1400HV. 300g The coating of FIG. 3 was subjected to abrasion testing (as described above) and the abrasion resistance factor (R) of the coating was determined to be 19.8 based on contact of the coating with a fine abrasive medium of 5 micron alumina square powder. A rotary wet wheel abrasion test yielded a wear resistance of 0.134 mm per 1000 revolutions.3 A wear scar was revealed with a volume loss of material of 0.023 μm. Testing confirmed that the coatings prepared according to the R-values ​​as shown in Table 1 exhibited a reduced amount of coating loss compared to conventional wear resistant coatings. The surface roughness of the wear scar was measured to increase by only 0.023 μm Ra and only 0.403 μm Rmax after microabrasion testing.

[0040] Both Examples 1 and 2 verified that the R-value is a reliable measure of the expected performance of the reinforced compounded coating against wear and erosion resulting from the coating coming into contact with a specific fine abrasive particle of a given size, as shown in Table 1.

[0041] Comparative Example 1 A carbide-based coating having a proportion of 86 wt. % WC, 10 wt. % Co, and 4 wt. % Cr was prepared using a conventional HVOF process without premixing and tested as described above. The coating was determined to have a mean free path of 0.566 microns, which was significantly higher than that measured in Examples 1 and 2. The coated specimens prior to wear testing were observed to exhibit substantial porosity and substantial oxide content based on optical microscopy analysis. Figure 4 shows an optical micrograph of the coating at 500x magnification. Substantial coating porosity was observed in Figure 4, as indicated by the presence of numerous pores. Substantial coating oxide was observed, as indicated by the presence of numerous "stringers". The hardness was measured at 1300HV. 300g The coating of FIG. 4 was subjected to fine abrasion testing (as described above) and the abrasion resistance factor (R) of the coating was determined to be 8.8, based on contact of the coating with a fine abrasive medium of 5 micron alumina square powder. A rotary wet wheel abrasion test yielded a wear resistance of 0.183 mm per 1000 revolutions. 3A wear scar was revealed with a volume loss of material of 0.119 μm. Testing confirmed that coatings not prepared according to the R-value ranges in Table 1 exhibited a significant increase in the amount of coating loss compared to the coatings of Examples 1 and 2. The surface roughness of the wear scar was measured to increase after microabrasion testing to an Ra of 0.119 μm and an Rmax of 2.41 μm, indicating significantly higher damage than that encountered with the coatings of Examples 1 and 2.

[0042] Test data has confirmed that producing a wear resistant coating having an abrasion resistance factor (R) equal to or greater than a minimum R-value of 12.5 but equal to or less than a maximum R-value of 30, in contact with an abrasive particle size of 4 to 7 microns, can produce an improved wear resistant coating having substantially reduced porosity, substantially reduced oxides, and substantially reduced material wear loss, as compared to conventional wear resistant coatings that do not have an R-value within the required range.

[0043] While what are considered to be particular embodiments of the invention have been shown and described, it will of course be understood that various modifications and changes in form or detail can be readily made without departing from the spirit and scope of the invention. It is therefore intended that the invention not be limited to the exact forms and details shown and described herein, nor be limited to anything less than the full scope of the invention disclosed herein and claimed below.

Claims

1. 1. An improved coated article for use in producing a battery electrode material containing fine abrasive particles, said improved coated article comprising: an article adapted to contact the fine abrasive particles; a wear-resistant coating on a surface of the article, the wear-resistant coating comprising one or more hard phases of a carbide-based material in an amount of 83 to 94 weight percent based on the total weight of the wear-resistant coating, with the balance being a metallic binder; the wear resistant coating has an abrasion resistance coefficient designated as (R) that ensures that a majority of the fine abrasive particles adapted for contact with the improved coated article are located on the hard phase, thereby reducing or minimizing contact between the fine abrasive particles and the metal bond, the abrasion resistance coefficient (R) being defined as the ratio of the average size of the fine abrasive particles to the mean free path of the metal bond; The improved coated article wherein said wear resistance factor (R) has a value in the range of 1 to 65 for a corresponding average size of said fine abrasive particles in the range of 0.5 to 15 microns.

2. 10. The improved coated article of claim 1 further comprising an oxide content of less than 2.5 volume percent.

3. 10. The improved coated article of claim 1 further comprising less than 1 volume percent porosity.

4. 950HV 300g 10. The improved coated article of claim 1 further comprising a Vickers hardness of at least 100%.

5. The carbide material is WC, CrC, (W,Cr)C, TiC, VC, NbC, B 4 2. The improved coated article of claim 1, wherein said metal is selected from the group consisting of C, and SiC.

6. 1. An enhanced wear resistant coating having a porosity of less than 1 volume percent and an oxide content of less than 2.5 volume percent, said wear resistant coating further comprising a hard phase and a metallic binder, whereby said wear resistant coating has a wear resistance coefficient designated as (R), said wear resistance coefficient (R) being defined as the ratio of an average size of fine abrasive particles to the mean free path of said metallic binder, said wear resistance coefficient (R) having a value in the range of 1 to 65 for a corresponding average size of said fine abrasive particles in the range of 0.5 to 15 microns.

7. 950HV 300g 7. The enhanced wear resistant coating of claim 6, further comprising a Vickers hardness of at least 1000 nm.

8. The hard phase is WC, CrC, (W,Cr)C, TiC, VC, NbC, B 4 7. The enhanced wear resistant coating of claim 6, wherein the metal binder is selected from the group consisting of C, SiC, and diamond, and the metal binder is selected from the group consisting of Co, CoCr, Ni, NiCr, Mo, Fe, FeCrAl, FeCr, FeB, FeAl, TiAl, and Ti.

9. 1. An enhanced wear resistant coating suitable for protection against abrasive microparticles, said wear resistant coating having a porosity of less than 1 volume percent and an oxide content of less than 2.5 volume percent, said wear resistant coating comprising a hard phase and a metallic binder, said wear resistant coating configured to substantially reduce wear of said metallic binder with a wear resistance factor designated as (R), defined as the ratio of the average size of said abrasive microparticles to the mean free path of said metallic binder, said wear resistance factor having a value in the range of 1 to 65; However, when the average size of the abrasive fine particles is 0.5 microns, the wear resistance coefficient (R) is in the range of 1 to 3; However, when the average size of the abrasive fine particles is 0.75 microns, the wear resistance coefficient (R) is in the range of 2 to 4; However, when the average size of the abrasive fine particles is 1 micron, the wear resistance coefficient (R) is in the range of 3 to 5; However, when the average size of the abrasive fine particles is in the range of 2 to 3 microns, the wear resistance coefficient (R) is in the range of 6 to 14; However, when the average size of the abrasive fine particles is in the range of 4 to 7 microns, the wear resistance coefficient (R) is in the range of 13 to 30; However, when the average size of the abrasive microparticles is in the range of 8 to 15 microns, the wear resistance factor (R) is in the range of 25 to 65.

10. 10. The wear-resistant coating of claim 9, wherein the abrasive microparticles are a battery electrode material.

11. The abrasion resistant coating has a hardness of 950HV 300g 10. The wear resistant coating of claim 9, further comprising a Vickers hardness of at least 1000 nm.

12. The hard phase is WC, CrC, (W,Cr)C, TiC, VC, NbC, B 4 10. The wear resistant coating of claim 9, wherein the metal binder is selected from the group consisting of C, SiC, and diamond, and the metal binder is selected from the group consisting of Co, CoCr, Ni, NiCr, Mo, Fe, FeCrAl, FeCr, FeB, FeAl, TiAl, and Ti.

Citation Information

Patent Citations

  • Method for carrying out high velocity oxy-fuel spraying on surface of roller of lithium battery pole piece rolling machine

    CN105441857A

  • Sintered thermal spray powder based on molybdenum carbide

    JP2016540883A

  • One-step method for producing liquid-tight, fully dense coatings

    JP2021530622A

  • High Strength Corrosion Resistant High Velocity Oxy Fuel (HVOF) Coating for Downhole Tools

    US20150322719A1